Embryonic thermal manipulation has short and long-term effects on the development and the physiology of the Japanese quail - Vitorino Carvalho, Anaïs (PLoS One, 2020)
In vertebrates, the embryonic environment is known to affect the development and the health of individuals. In broiler chickens, the thermal-manipulation (TM) of eggs during the incubation period was shown to improve heat tolerance at slaughter age (35 days of age) in association with several modifications at the molecular, metabolic and physiological levels. However, little is known about the Japanese quail (Coturnix japonica), a closely related avian species widely used as a laboratory animal model and farmed for its meat and eggs. Here we developed and characterized a TM procedure (39.5°C and 65% relative humidity, 12 h/d, from days 0 to 13 of incubation) in quails by analyzing its short and long-term effects on zootechnical, physiological and metabolic parameters. Heat-tolerance was tested by a heat challenge (36°C for 7h) at 35 days of age. TM significantly reduced the hatching rate of the animals and increased mortality during the first four weeks of life. At hatching, TM animals were heavier than controls, but lighter at 25 days of age for both sexes. Thirty-five days after hatching, TM decreased the surface temperature of the shank in females, suggesting a modulation of the blood flow to maintain the internal temperature. TM also increased blood partial pressure and oxygen saturation percentage at 35 days of age in females, suggesting a long-term modulation of the respiration physiology. Quails physiologically responded to the heat challenge, with a modification of several hematologic and metabolic parameters, including an increase in plasma corticosterone concentration. Several physiological parameters such as beak surface temperature and blood sodium concentration revealed that TM birds responded differently to the heat challenge compared to controls. Altogether, this first comprehensive characterization of TM in Japanese quail showed durable effects that may affect the response of TM quails to heat.